Cochlear Implantation for Cochlear Nerve Deficiency - Li, Yongxin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Having been found in 3%-21% patients with congenital sensorineural deafness, cochlear nerve deficiency (CND) is defined by a small or absent cochlear nerve. This book describes the updated information on the embryology, pre- and post- operative auditory, electrophysiology and vestibular aspects of CND. What$1 (Bs more, the cochlear implantation (CI) strategy and CI outcomes as well as comparison with normal patients will be discussed in details with selected cases and high resolution illustrations. It will be a valuable reference for otologists, audiologists and practitioners who would like to understand more about CND and choose optimal clinical strategy of CI surgery for CND.s
Phylogeny and Embryology of Cochlear Nerve Deficiency -- Pathogen of Cochlear Nerve Deficiency -- Radiological Aspect Progress in CND -- Preoperative Auditory and Electrophysiology Evaluation for CND -- Cochlear Implantation Strategy for CND -- Cochlear Implant Programming for Patients with Cochlear Nerve Deficiency -- Postoperative Electrophysiology Test for Cochlear Nerve Deficiency -- Cochlear Implantation Outcomes of Cochlear Nerve Deficiency -- Balance and Vestibular Function of Cochlear Nerve Deficiency -- Special Cases Reports.
Keywords: Otorhinolaryngology; Otorhinolaryngology; Cochlear Implantation -- methods; Hearing Loss -- rehabilitation; Cochlear Implants